Politainment in campaign: engagement on Twitter social audience - Zamora-Medina, Rocío (2021)
The presence of candidates in politainment programs during electoral campaigns has already become a general practice in Spain. Considering that the vast majority of reactions on social media refer to the content or guests of television programs (D'heer & Verdegem, 2014), these reactions can be used to determine to what extent these shows contribute to improving the political knowledge of each candidate through the eyes of the audience (Boukes & Trilling, 2017). This research is based on some previous studies supporting the impact of political infotainment programs on promoting political engagement among the social audience, (Moy, Xenos & Hess, 2005) and in terms of benefits for politicians regarding their public image and outreach to new audiences (Teruel, 2016). However, this study aims to go further, specifying what type of content promotes greater public involvement.  For that purpose, we conducted a comparative and quantitative empirical analysis of the social conversation generated from main hashtag designed for each candidate on the tv show El Hormiguero during 2019 elections campaign. Concretely, a sample of 249 tweets were analysed, selected among those with a higher level of interaction among prosumers – metrics of follow-up, virality and thematic- taking as a case study the public appearances of Pablo Iglesias (Unidas Podemos), Pablo Casado (PP), Albert Rivera (Ciudadanos), Santiago Abascal (VOX) and Íñigo Errejón (Más País) in the program El Hormiguero during the 2019 electoral campaign in Spain. Results show the remarkable presence of contents that do not promote the constructive knowledge of candidates. However, depending on certain variables, this content fosters citizen engagement as part of the campaign strategy.